PERBANDINGAN HASIL BELAJAR FISIKA YANG MENGGUNAKAN MODEL PEMBELAJARAN MAKE A MATCH DENGAN MODEL PEMBELAJARAN COOPERATIVE SCRIPT DI SMA - Octaviano Octaviano; Vina Serevina; Anggara Budi Susila (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
The research aims to determine the comprison result of learning physics by using model Make A Match with Cooperative Script in high school.This research was conducted at SMAN 53 Jakarta in February-April 2015. The sample used in a class X MIA 2 as an experimental class 1, and X MIA 1 as an experimental class 2 respectively of 36 students who have the same condition.The research method is quasi experiment, the research instrument in the form of multiple choice questions with a number of about 30 items. Using the price obtained Normality Test Chi Square cunt  Chi Square table, for class 1 is 7,86642  11,070 and experimen class 2 that 6,9326  11,070, based on data from second class of normal distribution. Homogeneity test resuls obtained for  is 1,275  2,52 so the data is homogeneous. Based on hypothesis testing using t-test showed  (2,015) and the value of  (1,66691) at significance level  by dk=(36-36)-2=70. Because  then Ho is rejected and Ha accepted. It can be concluded that students who use learning models make a match higher than students who use Cooperative Script learning model.Keywords: Make A Match, Cooperative Script, Learning Outcomes.